Molecular cloning of a Pseudomonas syringae pv. syringae gene cluster that enables Pseudomonas fluorescens to elicit the hypersensitive response in tobacco plants. - Huang, H C (1988)
A cosmid clone isolated from a genomic library of Pseudomonas syringae pv. syringae 61 restored to all Tn5 mutants of this strain studied the ability to elicit the hypersensitive response (HR) in tobacco. Cosmid pHIR11 also enabled Escherichia coli TB1 to elicit an HR-like reaction when high levels of inoculum (10(9) cells per ml) were infiltrated into tobacco leaves. The cosmid, which contains a 31-kilobase DNA insert, was mobilized by triparental matings into Pseudomonas fluorescens 55 (a nonpathogen that normally causes no plant reactions), P. syringae pv. syringae 226 (a tomato pathogen that causes the HR in tobacco), and P. syringae pv. tabaci (a tobacco pathogen that causes the HR in tomato). The plant reaction phenotypes of all of the transconjugants were altered. P. fluorescens(pHIR11) caused the HR in tobacco and tomato leaves and stimulated an apparent proton influx in suspension-cultured tobacco cells that was indistinguishable from the proton influx caused by incompatible pathogenic pseudomonads. P. syringae pv. tabaci(pHIR11) and P. syringae pv. syringae 226(pHIR11) elicited the HR rather than disease symptoms on their respective hosts and were no longer pathogenic. pHIR11 was mutagenized with TnphoA (Tn5 IS50L::phoA). One randomly chosen mutant, pHIR11-18, no longer conferred the HR phenotype to P. fluorescens. The mutation was marker-exchanged into the genomes of P. syringae pv. syringae strains 61 and 226. The TnphoA insertions in the two pseudomonads abolished their ability to elicit any plant reactions in all plants tested. The results indicate that a relatively small portion of the P. syringae genome is sufficient for the elicitation of plant reactions.